2021
DOI: 10.28991/esj-2021-01252
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Digital Skills in Higher Education Institutes: During the COVID-19 Pandemic

Abstract: Objectives: Recently, due to special conditions that the global community is experiencing (Covid-19), there is growing interest in research in educational leadership, especially in higher education, which will create an environment embedded in a collaborative culture, open to improvements, testing, and often unexpected challenges. Among the different forms of educational leadership, transformational leadership is recognized as the most appropriate for application in higher education, as it focuses on the divis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 26 publications
3
42
0
6
Order By: Relevance
“…In this critical time, the role of leadership cannot be ignored (Billings et al, 2020;Sant'Ana et al, 2020;Zhao et al, 2020a). While studies have shown that transformational leadership, inclusive leadership and servant leadership seems to be a suitable leadership style for managing employees working in education sector during this pandemic, there is no evidence on the effectiveness of these leadership styles in hospitals settings and occupational safety offered by these leadership styles (Azizaha et al, 2020;Fournier et al, 2020;Zhao et al, 2020b;Antonopoulou et al, 2021;Piorun et al, 2021). There is an urgent need to implement a leadership style that has a prime focus on the occupational safety of employees so that healthcare workers may feel safe in the hospitals while serving the COVID-19 patients (Labrague and De los Santos, 2020;Rosa et al, 2020;Zhao et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In this critical time, the role of leadership cannot be ignored (Billings et al, 2020;Sant'Ana et al, 2020;Zhao et al, 2020a). While studies have shown that transformational leadership, inclusive leadership and servant leadership seems to be a suitable leadership style for managing employees working in education sector during this pandemic, there is no evidence on the effectiveness of these leadership styles in hospitals settings and occupational safety offered by these leadership styles (Azizaha et al, 2020;Fournier et al, 2020;Zhao et al, 2020b;Antonopoulou et al, 2021;Piorun et al, 2021). There is an urgent need to implement a leadership style that has a prime focus on the occupational safety of employees so that healthcare workers may feel safe in the hospitals while serving the COVID-19 patients (Labrague and De los Santos, 2020;Rosa et al, 2020;Zhao et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, digital transformation can be applied at both organizational and individual levels, which is a great advantage, so organizations need to change operating modes, leaders need to proactively absorb and adapt. To achieve efficiency in the digital age became a popular phenomenon [66]. In fact, there is still confusion that a digital leader is the leader of a business or an organization engaged in digital activities.…”
Section: -Background That Drives Digital Transformationmentioning
confidence: 99%
“…However, a digital leader should be understood as someone with digital skills (digital knowledge) with business knowledge and strategic thinking. According to Antonopoulou et al (2021) [66], the digital leader is characterized by strategic leadership, business knowledge to add value to the organization, and digital comprehension to exploit technology trends. By the end of 2020, the great crisis caused by Covid-19 caused strong disturbances in the social life on a worldwide scale, forcing countries to enter a period of accelerating the application of digital technology [67].…”
Section: -Background That Drives Digital Transformationmentioning
confidence: 99%
See 2 more Smart Citations